Różnorodność biologiczna jako czynnik aktywizacji ekonomicznej północno-wschodniej Polski - Poskrobko, Tomasz (Biodiversity as a factor of economic revival of North-Eastern Poland, 2007)
The main aim of the article is to assess the possibility of economic activation of local community trough sustainable use of biodiversity. The author advances a hypothesis that the diversity of nature is a wealth not only in ecological but also in economic sense. Both the European Union and Poland agreed that the biodiversity protection is a necessity. Unfortunately, the main burden of that protection lies in the hands of local communities. Increased restrictions on economic activities cause that the possibilities of local development are fewor. The author, according to sustainable development assumptions, tries to point other possibilities of economic activation of local communities trough sustainable biodiversity use.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 224-234